Developing Entrepreneurial Interest and Student Independence through Project-Based Entrepreneurship Learning: Mengembangkan Minat Wirausaha dan Kemandirian Mahasiswa melalui Pembelajaran Kewirausahaan Berbasis Proyek - Erwantiningsih, Eni; Wahyuni, Hari; Immadudin, Waladi (Pedagogia : Jurnal Pendidikan, 2021)
The purpose of this study was to determine (1) How the contribution of project-based entrepreneurship learning; (2) What is the student's entrepreneurial interest; (3) How independent are students; (4) How does project-based entrepreneurship learning affect students' entrepreneurial interest and independence. The method in this research is quantitative survey. According to the results of the study, the t-count value is 5.517 and the t-table number is 2.002, so that t-count> t-table, which means that there is a significant influence between Project-Based Learning on Entrepreneurial Interest, while the magnitude of the influence is obtained a coefficient value of 0.669 for the effect of learning. project based on entrepreneurial interest. Meanwhile, for the effect of entrepreneurship learning on student independence, the t-count is 5.993 and the t-table number is 2.002, so that t-count> t-table. This means that there is a significant influence between project-based learning on independence. There is also a coefficient value of 0.696, which means that when there is an increase in project-based learning, it will increase Independence by 0.696. Meanwhile, the correlation coefficient value is 0.618 and the coefficient of determination (R2) is 0.382. This means that there is an influence between the Project-Based Learning variable on Independence of 38.2% while the remaining 61.8% is influenced by other variables that the researchers did not involve in this study.